Fooled by Randomness: Investor Perception of Fund Manager Skill - Heuer, Justus; Merkle, Christoph; Weber, Martin (Review of Finance, 2017)
Return-chasing investors almost exclusively consider top-performing funds for their investment decisions. When drawing conclusions about the managerial skill of these top performers, they tend to neglect fund volatility and the cross-sectional information contained in the number of funds and the distribution of skill. In multiple surveys of sophisticated retail investors, we show that they do not fully understand the role of chance in experimental samples of fund populations. Respondents evaluate each fund in isolation and do not sufficiently account for fund volatility. They confuse risk taking with manager skill and are thus likely to over-allocate capital to lucky past winners.